Bertemu Dengan Realitas: Belajar Dari Fenomenologi Husserl - Emanuel Prasetyono (Arete, 2012)
Phenomenology would like to restore man’s process of gaining knowledge in the relationship between the ideal transcendental subject which tends to the object, and the appearing object to man’s consciousness, precisely after the long history of tumult and tension between rationalism and empiricism on the valid ground of knowledge. In phenomenology, human consciousness brings man about being capable of transcending himself, his livelihood, the world, and others. In phenomenology, human reason now is as being-in the world, in its relationship with consciousness itself, the world, and others. That human life, the world, and nature live in peace and truth is phenomenology’s contribution to life that we hope it be so.